Annual patterns of phytoplankton density and primary production in a large, shallow lake: The central role of light - Torremorell, Ana María (2009)
Summary: We studied the seasonal dynamics of suspended particulate matter in a turbid, large shallow lake during an annual period (2005-06). We relate the patterns of seston concentration (total suspended solids), phytoplankton biomass and water transparency to the seasonal pattern of incident solar radiation (I0). We also report the seasonal trends of phytoplankton primary production (PP) and photosynthesis photoinhibition due to photosynthetically active radiation (PAR) and ultraviolet radiation (UVR) (Iβ and UV50). We first collected empirical evidence that indicated the conditions of light limitation persisted during the study period. We found that the depth-averaged irradiance estimated for the time of the day of maximum irradiance (Imean-noon) was always lower than the measured onset of light saturation of photosynthesis (Ik). We then contrasted the observations with theoretical expectations based on a light limitation scenario. The observed temporal patterns of seston concentration, both on a volume and area basis, were significantly explained by I0 (R2 = 0.39 and R2 = 0.37 respectively). The vertical diffuse attenuation coefficient (kdPAR) (R2 = 0.55) and the depth-averaged irradiance (Imean) (R2 = 0.66), significantly increased with the I0; while the irradiance reaching the lake bottom (Iout) significantly decreased with the incident irradiance (R2 = 0.49). However, phytoplankton biovolume maxima were not coincident with the time of the year of maximum irradiance. A significant positive relationship was observed between PP estimated on an area basis and I0 (R2 = 0.51, P < 0.001). In addition, the parameters describing the photosynthetic responses to high irradiances displayed marked seasonal trends. The photosynthesis photoinhibition due to PAR as well as to UV were significantly related to incident solar radiation (PAR: R2 = 0.73; UV: R2 = 0.74). These results suggest adaptation of the phytoplankton community in response to changes in incident solar radiation.